Social mobility in industrial society - Lipset, Seymour Martin; Bendix, Reinhard (London, 1959)
In a careful analysis of the existing literature, the authors marshal an imposing array of evidence in support of their major argument that social mobility is an integral and continuing aspect of the process of industrialization. This classic volume continues to be a basic reference source in the field of occupational mobility.
Keywords: Sociology